2004 Proceedings. 54th Electronic Components and Technology Conference (IEEE Cat. No.04CH37546)
DOI: 10.1109/ectc.2004.1320280
|View full text |Cite
|
Sign up to set email alerts
|

Models for reliability prediction of fine-pitch BGAs and CSPs in shock and drop-impact

Abstract: Drop-induced failures are most dominant in portahle electronic products. In this &dy; explicit fmite element models ,have been used to study the transient dynamics of printed circuit hoards during drop from 6ft. Methodologies for modeling components using smeared property formulations have been investigated. Reduced integration element formulations examined. includeshell and solid elements. . Model predictions have been validated with experimental data. Results show that models with smeared properties can pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(23 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…8). Lall et al [8] also reported PCB resin cracks in the drop test of a 8x8mm chip scale package. As for the PQFP packages where failures were also recorded, they were not due to solder joint crack but component failure instead.…”
Section: Test Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…8). Lall et al [8] also reported PCB resin cracks in the drop test of a 8x8mm chip scale package. As for the PQFP packages where failures were also recorded, they were not due to solder joint crack but component failure instead.…”
Section: Test Resultsmentioning
confidence: 93%
“…From the physics of failure characterized in the drop test, improved solutions to IC package design can be implemented to avoid such drop related failures in service. Research on drop impact testing and finite element modeling investigations [1][2][3][4][5][6][7][8][9][10] are further needed for developing a design-for-reliability (DFR) methodology [5] for drop impact reliability qualification of board-level soldered assemblies. Drop impact responses such as acceleration and strains experienced by the PCB are obtained and studied to investigate the mechanisms of the solder joint failure modes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, for the PBGA package with OSP finish case, PCB copper traces breakage and resin cracks were the contributing factor for failure [1]. Lall et al [9] also reported PCB resin cracks in the drop test of chip scale package. As for the PQFP packages, failures were not due to solder joint crack but component failure with the lead fingers breaking off from the mold compound due to fatigue of leads.…”
Section: Board Level Drop Test and Analysismentioning
confidence: 95%
“…As explained earlier, existing damage models in literature [3][4][5][6][7][8][9][10][11] do not address the rate-dependence of durability, for dynamic loading of PWAs. We propose a new mechanistic, rate-dependent durability estimation model in this paper that focuses on solder failure.…”
Section: Damage Modelmentioning
confidence: 99%
“…Empirical models have been developed to quantify durability as a function of PWA strain [3][4][5] and PWA displacement [6]. In some cases, Finite Element Analysis (FEA) with rate-independent material properties has been used to quantify durability in terms of solder stress [7][8][9] or solder strain [10,11] and to develop failure envelopes based on normal and shear forces in the solder [12].…”
Section: Introduction and Problem Statementmentioning
confidence: 99%